2020
DOI: 10.31234/osf.io/e967j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationships between Psychological Contract Breach and Employee Well-Being and Career-Related Behavior: The Role of Occupational Future Time Perspective

Abstract: Relationships between psychological contract breach and employee well-being and career- related behavior cannot sufficiently be explained by social exchange and reciprocity theories, yet the alternative mechanisms underlying these associations are currently not well understood. Based on the psychological contract perspective on careers, the goal of this study was to examine indirect effects of psychological contract breach on emotional engagement, emotional exhaustion, and career-related behavior through two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…These findings match the results of Kader et al 23 , who postulated that career development opportunities correlated significantly with job burnout. This study corroborates the findings of Zacher and Rudolph 52 that employees with a positive outlook on their future career prospects tend to be more productive and content with their jobs, and this has a beneficial effect on their well-being and behaviour. Furthermore, a recent study by Koo et al 56 found that organizational commitment is a key factor in job burnout.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings match the results of Kader et al 23 , who postulated that career development opportunities correlated significantly with job burnout. This study corroborates the findings of Zacher and Rudolph 52 that employees with a positive outlook on their future career prospects tend to be more productive and content with their jobs, and this has a beneficial effect on their well-being and behaviour. Furthermore, a recent study by Koo et al 56 found that organizational commitment is a key factor in job burnout.…”
Section: Discussionsupporting
confidence: 90%
“…This in turn increases their work engagement and performance, making them less likely to leave their jobs. This result is further supported by the results of prior studies by Brunner et al 45 on work conditions, Falatah et al 21 on job security, Zacher and Rudolph 52 on perceived career development opportunities, Oyewobi et al 24 on affective organizational commitment, and Li et al 25 on perceived organizational support, which all demonstrate that negative attitudes towards one’s job can lead to an increased intention to quit, and that these factors significantly contribute to the development of employee well-being symptoms.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations